1970
DOI: 10.1063/1.1692913
|View full text |Cite
|
Sign up to set email alerts
|

Linear Instability of Asymmetric Flow in Channels

Abstract: A study of the linear stability of asymmetric channel flows is presented. Three one-parameter families of basic velocity which possess, respectively, no, one, and two inflection points are treated. The competing effects of stabilizing asymmetry and destabilizing vorticity distributions are discussed. An inviscid wave speed theorem which extends a result of Stuart to flows with two inflection points is proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…This was done for a range of the parameters (a, BJ. The results agree with those of Fu & Joseph (1970) and are illustrated in figure 1. As a check, the eigenvalue c, was also computed from the adjoint problem (7.5) using the conditions (5.12).…”
Section: )supporting
confidence: 87%
“…This was done for a range of the parameters (a, BJ. The results agree with those of Fu & Joseph (1970) and are illustrated in figure 1. As a check, the eigenvalue c, was also computed from the adjoint problem (7.5) using the conditions (5.12).…”
Section: )supporting
confidence: 87%
“…Considering the numerical solution of the Navier-Stokes equation and the least squares fit of flow parameters, Kachuma and Sobey [9] showed the existence of a flow region after the barrier/step where the above model's basic flow (Equation (9) with β 1 = β 2 = 0) fits well to true longitudinal velocity. Our approximated mean flow solution U(y) is similar to the polynomial-type solution suggested by Fu and Joseph [11] for asymmetric flow in channels. When σ 1 = σ 2 = 0, the limiting flow is plane Poiseuille in a slipper channel [31], and in addition, if β 1 = β 2 = 0, then it is plane Poiseuille in a rigid channel (with U(y) = 3 2 (1 − y 2 )).…”
Section: Mean Velocity Profilementioning
confidence: 53%
“…The mean velocity field of the fully developed flow at that particular position can be approximated by U = (U(y), 0), which satisfies the condition U(y) = ∓β i U y (y) at the walls (y = ±1). Hereat, following the formulation of Fransson and Alfredsson [8], Kachuma and Sobey [9] and Fu and Joseph [11], we have considered a typical mean velocity profile, which takes into account the effects of asymmetry together with wall slip and is given by…”
Section: Mean Velocity Profilementioning
confidence: 99%
“…Gad-el-Hak (2002), Babenko and Kozlov (1972) and Fu and Joseph (1970) reported that although compliant materials can stabilize different types of instabilities, they might cause other types of instabilities such as hydro-and aero-elastic instabilities. In fact, it was noticed by researchers that stable fluid flows inside rigid channels became unstable in deformable channels.…”
Section: Introductionmentioning
confidence: 99%